Strategi Pengembangan Wisata Puncak Jowin Untuk Meningkatkan Jumlah Kunjungan Wisatawan Di Kabupaten Tulungagung - Antamayuan S, Moch Verry Martin; Preswari, Yasmin Indra; Putri, Winda Istiqlaliya (Jurnal Ekonomi, Bisnis dan Manajemen, 2024)
Thesis with the title Jowin Peak Tourism Development Strategy to Increase the Number of Tourist Visits in Tulungagung Regency" written by Yasmin Indra Preswari, Moch. Verry Martin A.S, M Islamic Sharia Tourism Study Program, Department of Management and Business, Faculty of Islamic Economics and Business, Sayyid Ali Rahmatullah Tulungagung State Islamic University who was supervised by Dr. Deny Yudiantoro, S.AP., M.M., The research in this thesis is based on the importance of tourism development strategies because the main reason for tourism development in a tourist destination, whether locally, regionally or nationally in a country, is closely related to the economic development of that region or country. The focus of research in writing this thesis is (1) What is the tourism development strategy to increase tourist visits to the Puncak Jowin Tulungagung tourist attraction? (2) What is the strategy for developing human resources to increase tourist visits to the Puncak Jowin Tulungagung tourist attraction? (3) What is the most effective role of media in reaching and influencing the target audience of tourists, especially in the context of digitalization and developments in information technology? This type of research is field research using a descriptive method approach. In collecting data researchers used the method of observation, interviews, and documentation. Researchers double-checked to obtain the data obtained and used triangulation techniques, with the aim of obtaining data validity. After that, analyzing it through data reduction and making conclusionsng the validity of the data uses source triangulation and technical triangulation. Based on the results of data analysis, it can be concluded that the research results show that (1) tourism development strategies to increase tourist visits to the Puncak Jowin Tulungagung tourist attraction are carried out in various ways, including strategies including adding tourist attractions, developing accessibility, developing amenities, developing public facilities. the role of government. (2) human resource development strategy to increase tourist visits to the Puncak Jowin Tulungagung tourist attraction by implementing a capacity building strategy which includes Human Resource (HR) Development, Strengthening organization, Institutional reform (institutional reform) (3) Media strategy that most effective in reaching and influencing the target audience of tourists, by referring to technical and practical means. by implementing promotions on various social media platforms such as Facebook, Instagram, and Tiktok to influence the audience of data tourists to Puncak Jowim tourism.